Obesity and Preeclampsia: Common Pathophysiological Mechanisms - Lopez-Jaramillo, Patricio; Barajas, Juan; Rueda-Quijano, Sandra M.; Lopez-Lopez, Cristina; Felix, Camilo (Frontiers in Physiology, 2018)
Preeclampsia is a disorder specific of the human being that appears after the 20 weeks of pregnancy and it is characterized by new onset of hypertension and proteinuria. Abnormal placentation and reduced placental perfusion associated to impaired trophoblast invasion and alteration in the compliance of uterine spiral arteries are the early pathological findings that are present before the clinical manifestation of preeclampsia. Later on appear the endothelial and vascular dysfunction that are responsible by the characteristic vasoconstriction of the preeclampsia. Different nutritional risk factors as a maternal deficit in the intake of calcium, protein, vitamins and essential fatty acids, has been shows to play a role in the genesis of preeclampsia, but also an excess of weigh gain during pregnancy or a pre-pregnancy state of obesity and overweigh, that are associated to hyperinsulinism, insulin resistance and maternal systemic inflammation are proposed as one of the mechanism that conduce to endothelial dysfunction, hypertension, proteinuria, thrombotic responses, multi-organ damage, and high maternal mortality and morbidity. Moreover, it has been demonstrated that pregnant women that suffer preeclampsia will have an increased risk of future cardiovascular disease and related mortality in her later life. In this article we will discuss the result of studies performed in different populations that have show an interrelationship between obesity and overweigh with the presence of preeclampsia and the later risk of cardiovascular disease. Moreover, we will review some of the common mechanisms that explain this interrelationship, particularly the alterations in the L-arginine/nitric oxide pathway as a crucial mechanism that are common to obesity, preeclampsia and cardiovascular diseases.